Analisis Strategi Pemasaran Dengan Memanfaatkan Media Sosial Pada Usaha Vaie Gift - Patricia, Veren; Aldo, Fredy; Rahrdjo, Kusuma Adi (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
Indonesia has the potential in the form of creative industries, one of the products produced is in the form of various handicrafts and has the potential to develop. Making handicrafts is currently being done by many people in doing entrepreneurship, one of which is making gift bouquets. The gift bouquets produced also vary, such as flower bouquets, money bouquets, snack bouquets and various other kinds of hampers whose contents can be adjusted according to consumer demand. By utilizing existing materials and creativity, it can create innovations and new job opportunities for the community. In running a business, the marketing process is also important. Therefore, strategies are needed in running a business so that the business can continue to grow and survive in the face of tight competition in the market. Seeing the state of the market, students can take advantage of these opportunities in running entrepreneurial programs held by campuses and students can apply accounting insights obtained during lectures when running their businesses. The Vaie Gift business is engaged in services and the products produced are in the form of bouquets and hampers. In carrying out its business, Vaie Gift develops marketing strategies and utilizes social media that is often used by the public